A REVIEW STUDY OF THE ROLE OF ARTIFICIAL INTELLIGENCE IN ENHANCING BANKING INNOVATION - Amodah Obaid Hussein (Scholars Digest Publishing, 2025)
The purpose of the current review study is to reveal the role of artificial intelligence in promoting banking innovation, and technology is one of the main factors shaping the business environment in the modern era, as it is the cornerstone of enhancing opportunities for survival, growth and sustainability. As a result of the rapid and continuous development in modern technologies, which have helped to innovate new means and methods in providing banking services to customers, artificial intelligence programmes have emerged that are based on advanced modern technologies. Accordingly, the problem of the study was formulated with an important question: to what extent can artificial intelligence promote banking innovation? This was explored through a review of current literature and previous research in this field. With the increasing reliance on technology in various aspects of life, we find that the adoption of artificial intelligence in making credit decisions within the banking sector constitutes a major shift towards more innovative, efficient and accurate financial services. With the promise of mitigating risk, reducing costs and improving the customer experience, AI-powered credit decision-making is not just a passing trend, but a fundamental development in banking.
Keywords: Artificial Intelligence, Distribution Channels, Banking Innovation.